Pengaruh Lingkungan, Disiplin, Dan Kepuasan Kerja Terhadap Tingkat Kinerja Karyawan Studi Kasus Karyawan (Studi Kasus Karyawan JNE Cabang Utama Surabaya) - Sonia Ismi Khaq; Siti Asiyah; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2021)
Abstract Humans are one of the important elements needed in an organization. Even a company or organization cannot run if there are no humans in it, even though the factors have been met, the company still requires the role of humans so that the company's performance runs effectively and efficiently. company or organization. PT. The Nugraha Ekakurir route or better known as JNE is a private courier and logistics service company that has been developing in Indonesia for a long time. The sample in this study included 56 respondent at JNE Surabaya.In this study, the researcher used a quantitative descriptive research method in which the researcher distributed questionnaires to analyze the results of the respondents' answers and then tested them to get answers to the formulated hypotheses. Based on the research that has been done by the researcher, a result is obtained, where simultaneously the work environment, work discipline, and job satisfaction have a significant effect on the level of employee performance in the main office of JNE Surabaya. And partially also obtained results that each variable also has a significant effect on the performance variable. Keyword : Work environment, Work discipline, Job satisfaction, performance